Administrators need to cultivate a culture of excellence, dynamism and strategic thinking - Mimi Rabita, Abdul Wahit (2020)
Pekan, 13 July 2020 - In the era of increasingly competitive globalisation, every organisation needs its employees to be more aggressive, creative, innovative, productive and dynamic to keep pace to achieve the organisation’s goals towards excellence.